Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Karyawan PT. Ekaputra Prada Indonesia - Veri afandi; Hammam Zaki; Ikbal Akhmad (PT. Karya Inovatif Nusantara, 2024)
This research aims to determine the effect of compensation and motivation on the performance of PT employees. Ekaputra Prada Indonesia. This type of research is quantitative research. Data analysis uses the multiple linear regression analysis method of Employee Performance as the dependent variable and two independent variables: Compensation and Motivation. The research sample was 70 respondents. The results of this research state that the compensation variable has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance.